Solutions to improve policies to increase income for poor households in Ngoc Hien district, Ca Mau province - Le, Văn Khoa; Nguyen, Quyết Thắng (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
This study was conducted to assess the current situation of poverty and analyze the impact of state policies on the income of poor households in Ngoc Hien district, thereby proposing some solutions to increase income for poor households. poor in Ngoc Hien district. Using secondary data sets on the results of implementation of poverty reduction policies in 2019, 2020 and 2021 in Ngoc Hien district, Ca Mau province; orientations, planning tasks in 2022. In addition, primary data collected by using a prepared outline to collect opinions of 75 poor households in colonial communes and research are 05 communes including: Tan An, Tan An Tay, Dat Mui, Tam Giang Tay, Vien An. The data analysis method used in this study is the relative and absolute comparison method; Descriptive statistics. The author proposes policy implications to improve income for poor households in Ngoc Hien district, Ca Mau province, including: (i) Fully and timely implementation of policies; (ii) Scaling up poverty reduction models; (iii) Improve the efficiency of capital use of poor households; (iv) The job creation needs to meet the social needs.